PENGARUH DURASI DAN JARAK PENGGUNAAN SMARTPHONE TERHADAP KELELAHAN MATA PADA MAHASISWA ARO GAPOPIN - Rangga Adhitia Hermawan; Lorentius Wahana Dika (Jurnal Mata Optik, 2022)
The research objective was to determine the relationship between distance and duration of smartphone use and eye fatigue complaints among students of ARO Gapopin. The sampling technique used a simple purposive sampling method with a sample size of 116 respondents obtained through an online questionnaire on the google form. The data analysis used was in multiple regression analysis using the SPSS application. The results of this study showed that there was no influence between variable duration and distance of smartphone use on complaints of eye fatigue. With significance values of 0.996 and 0.682.